Factors Contributing Pre-School Trainees Teachers Adoption of Virtual Learning Environment: Malaysian Evidence - Ibrahim, Mamat; Ahmad Shidki, Mat Yusoff; Wan Salihin Wong, Abdullah; Fahmi Zaidi, Abdul Razak (2015)
Virtual Learning Environment (VLE) has become the main mechanism in supporting on-line education either in primary or secondary school. Although VLE efforts are considered to be a significant corporate investment, many surveys indicate high drop-out rates or failures. This research uses an integrated model in order to assessing the influence of IS-oriented, psychological and behavioral factors on instructors’ adoption of virtual learning systems. Survey data collected from 76 pre-school teachers were analyzed using structural equation modeling to examine the theoretical model. The research results show that, perceived ease of use and compatibility increase pre-school teachers intention to use virtual learning systems; however, perceived ease of use is the most important factor affecting on intention and actual use of the system (adoption).